The Conversion of a Practice-Based Lifestyle Enhancement Program into a Formalized, Testable Program: From Texercise Classic to Texercise Select - Marcia G Ory; Matthew Lee eSmith; Doris eHowell (Frontiers Media S.A., 2015)
*